Effect of Ultrasound-Assisted Sodium Bicarbonate Treatment on Aggregation and Conformation of Reduced-Salt Pork Myofibrillar Protein - Kang, Zhuang-Li; Shang, Xue-Yan; Li, Yan-Ping; Ma, Han-Jun (Molecules (Basel, Switzerland), 2022)
To study the effects of an ultrasound (0, 30, and 60 min) and sodium bicarbonate (0% and 0.2%) combination on the reduced-salt pork myofibrillar protein, the changes in pH, turbidity, aggregation, and conformation were investigated. After the ultrasound-assisted sodium bicarbonate treatment, the pH increased by 0.80 units, the absolute value of Zeta potential, hydrophobic force, and active sulfhydryl group significantly increased (p < 0.05), and the turbidity and particle size significantly decreased (p < 0.05). Meanwhile, the fluorescence intensity decreased from 894 to 623, and the fluorescence peak showed a significant redshift, which indicated that the ultrasound-assisted sodium bicarbonate treatment exposed the non-polarity of the microenvironment in which the fluorescence emission group was located, leading to the microenvironment and protein structure of myofibrillar tryptophan being changed. Overall, an ultrasound-assisted sodium bicarbonate treatment could significantly improve pork myofibrillar protein solubility and change the protein structure under a reduced-salt environment.